2007
DOI: 10.1128/jvi.00976-07
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic Cells Are Less Susceptible to Human Immunodeficiency Virus Type 2 (HIV-2) Infection than to HIV-1 Infection

Abstract: Human immunodeficiency virus type 1 (HIV-1) infection of dendritic cells (DCs) has been documented in vivo and may be an important contributor to HIV-1 transmission and pathogenesis. HIV-1-specific CD4+ T cells respond to HIV antigens presented by HIV-1-infected DCs and in this process become infected, thereby providing a mechanism through which HIV-1-specific CD4+ T cells could become preferentially infected in vivo. HIV-2 disease is attenuated with respect to HIV-1 disease, and host immune responses are thou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
32
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 81 publications
3
32
0
Order By: Relevance
“…The antibody used (KC57) has previously been shown to be specific for both HIV-2 Gag and HIV-1 Gag (35). We further confirmed the ability of the antibody to efficiently detect HIV-2 Gag by flow cytometry in activated PBMCs infected with the HIV-2 strains used in the current study (see Fig.…”
Section: Hiv-2 Infects the Human Thymussupporting
confidence: 70%
“…The antibody used (KC57) has previously been shown to be specific for both HIV-2 Gag and HIV-1 Gag (35). We further confirmed the ability of the antibody to efficiently detect HIV-2 Gag by flow cytometry in activated PBMCs infected with the HIV-2 strains used in the current study (see Fig.…”
Section: Hiv-2 Infects the Human Thymussupporting
confidence: 70%
“…The HIV-2 reverse transcriptase probably has a lower affinity for dNTPs (50), which may be detrimental for this virus in noncycling cells. It has been reported that DCs are less susceptible to HIV-2 than to HIV-1, when the infection is performed with cell-free virions (55). It will be worth examining whether HIV-2 more efficiently infects MDDCs by cellto-cell transmission and, if so, to evaluate the impact of Vpx on this phenomenon.…”
Section: Discussionmentioning
confidence: 99%
“…This requires further investigation because other groups have reported that dendritic cells are refractory to HIV-2 infection, which could in turn, restrict HIV-2 replication (65,66). Overall, an enhanced sensitivity of HIV-2 to host restriction factors may be crucial in limiting its replication initially, preventing further damage to the host immune system, providing the necessary window of opportunity for the subsequent induction and enactment of an effective T cell response that establishes and maintains control of the virus.…”
Section: Discussionmentioning
confidence: 99%